建築空間内における認知距離に影響する環境要因の検討 - 柳瀬, 亮太 (Cognitive Studies: Bulletin of the Japanese Cognitive Science Society, 1998)
Our movements to a destination tend to be done unconsciously, and shorter routes are usually selected. There are many studies on the relationship between physical distance and cognitive distance (e.g., Cadwallader, 1975, 1979; Sadalla, Staplin, & Burroughs, 1979; Sadalla & Magel, 1980; Sadalla & Staplin, 1980a, 1980b; Okamoto, 1983; Wakabayashi, 1989), but the results are still vague.The current study examined the factors which affect cognitive distance (CD). The subjects (Ss) have used the building of the experiment for more than 2years, and they estimated each walk of 10 routes in there. Each of those routes (50 m-144 m) is longer than the standard route (34 m). Before the estimation of the distance, the pictures of both ends of each route were given on display through World Wide Web with questionnaires. Ratio method was used to obtain the data of CD. The CD data were converted to logarithm, and compared with real walks. Then, the CD data of approximate walk were paired, and a pair of them was compared.As a result, six routes were estimated shorter than the real ones, and two routes were estimated longer. A pair of the CD data of approximate walk which are located right above or right below were estimated equally, but ones located on the same level and direction were estimated differently. It is suggested that the furniture (i.e., chair, garbage box), a varied structure (i.e., pillar) in building, and the lightness of route affect cognitive distance. Therefore, the CD in a building would depend on another factor that have not been suggested on studies in a large-scale environment, such as a city.